Implementation of discovery learning on electromagnetic wave material based on adsorption Congo Red by silica from Bengkulu beach sand - M. Lutfi Firdaus; Sasti Yuliafitri; Eko Swistoro; Ghufira Ghufira; Rendy W. Wardana (Universitas Negeri Yogyakarta, 2019)
This study aims to describe the differences in students’ critical thinking skill between class which use discovery learning and conventional learning in electromagnetic wave material. The research method used was a quasi-experimental method with a non-equivalent control group design which was conducted in MAS 01 Darussalam Kepahiang. In non-equivalent control group design, the sample (was) not taken randomly but by purposive sampling technique. The research sample taken by the researcher consists of two classes, (i.e.) the class XII A2 as an experimental class and the class XII A3 as a control class. Both classes were given a pretest to find out the students’ fundamental critical thinking skills and a posttest to find out the students' final critical thinking skills. This research was conducted in two meetings according to subchapters on electromagnetic wave material. Discovery learning model was applied in the experimental class with the steps of learning are stimulation, problem statement, data collection, data processing, verification, and generalization. The average value of critical thinking of the experimental class student was 65.7 and (the) control class was 48.12 with a value of sig. (2-tailed) = 0.000 less than sig. α = 0.05. Based on the results, it can be concluded that there is a significant difference in students’ ' critical thinking skills using the discovery learning model with the critical thinking skills of students using conventional learning.